2016
DOI: 10.1002/polb.24146
|View full text |Cite
|
Sign up to set email alerts
|

Application of SSA thermal fractionation and X-ray diffraction to elucidate comonomer inclusion or exclusion from the crystalline phases in poly(butylene succinate-ran-butylene azelate) random copolymers

Abstract: Poly(butylene succinate‐ran‐butylene azelate) random copolyesters were thermally fractionated by successive self‐nucleation and annealing (SSA). The samples before and after SSA were analyzed by differential scanning calorimetry (DSC) and X‐ray diffraction (WAXS and SAXS). WAXS results indicate that a small degree of comonomer inclusion is present in the crystalline phases that are formed in the copolymers depending on composition: a PBS‐like unit cell or/and a PBAz‐like unit cell, thus confirming the isodimor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…Other systems lie somewhere between. A study of a poly(butylene succinate‐ ran ‐butylene azelate) showed, by SAXS, an increase in lamellar thickness, as well as an increase in interlamellar amorphous thickness, which they associated with some degree of comonomer inclusion in the crystals, which they could adjust with suitable thermal treatments . This greater lamellar thickness at central compositions (for a given undercooling) might be associated with a smaller free energy change on crystallization than for the homopolymers due to the more random nature of the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other systems lie somewhere between. A study of a poly(butylene succinate‐ ran ‐butylene azelate) showed, by SAXS, an increase in lamellar thickness, as well as an increase in interlamellar amorphous thickness, which they associated with some degree of comonomer inclusion in the crystals, which they could adjust with suitable thermal treatments . This greater lamellar thickness at central compositions (for a given undercooling) might be associated with a smaller free energy change on crystallization than for the homopolymers due to the more random nature of the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…A study of a poly(butylene succinate-ran-butylene azelate) showed, by SAXS, an increase in lamellar thickness, as well as an increase in interlamellar amorphous thickness, which they associated with some degree of comonomer inclusion in the crystals, which they could adjust with suitable thermal treatments. 51 This greater lamellar thickness at central compositions (for a given undercooling) might be associated with a smaller free energy change on crystallization than for the homopolymers due to the more random nature of the crystal structure. Rather than a random incorporation of nonmatching monomers into the crystal structure, the PET/PEN system is thought, under suitable crystallization conditions, to cocrystallize by sequence matching with the local rejection of nonmatching sequences, as postulated by Lu and Windle.…”
Section: Crystallization Morphologymentioning
confidence: 99%
“… 39 On the other hand, SSA can be exploited also for the characterization of linear polymers, where fractionation occurs only for chain length differences, even if the fractionation is less efficient. 54 Thermal fractionation experiments on pCBT were performed setting as first T s temperature the T s,ideal determined in self-nucleation experiments, i.e., T s = 227 °C. The thermal protocol consisted in seven T s , from 227 °C down to 197 °C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…particular of random copolymers in which the crystallizable component is frequently interrupted (depending on composition) by the second component (e.g., random isodimorphic copolymers [5] ).…”
mentioning
confidence: 99%
“…The SSA fractionated material contains lamellae with a distribution of thickness (and a corresponding distribution of melting points) that is proportional to the defect or comonomer distribution along the crystallizable chains. [5] Such size distribution can be estimated, in some cases, e.g., multiblock copolymers. [6] In the case of polyolefins, in which the SSA technique has been widely used, the SSA has been recently used to perform branching analysis [7,8] and photodegradation studies, [9] among others.…”
mentioning
confidence: 99%